Frequency-Dependent Neural Activity in Patients with Unilateral Vascular Pulsatile Tinnitus - Han Lv; Pengfei Zhao; Zhaohui Liu; Guopeng Wang; Rong Zeng; Fei Yan; Cheng Dong; Ling Zhang; Rui Li; Peng Wang; Ting Li; Shusheng Gong; et al. (Neural Plasticity)
Previous resting-state functional magnetic resonance imaging (rs-fMRI) studies have shown that neurological changes are important findings in vascular pulsatile tinnitus (PT) patients. Here, we utilized rs-fMRI to measure the amplitude of low-frequency fluctuations (ALFF) in forty patients with unilateral PT and forty age-, gender-, and education-matched normal control subjects. Two different frequency bands (slow-4, 0.027–0.073 Hz, and slow-5, 0.010–0.027 Hz, which are more sensitive to subcortical and cortical neurological signal changes, resp.) were analyzed to examine the intrinsic brain activity in detail. Compared to controls, PT patients had increased ALFF values mainly in the PCu, bilateral IPL (inferior parietal lobule), left IFG (inferior frontal gyrus), and right IFG/anterior insula and decreased ALFF values in the multiple occipital areas including bilateral middle-inferior occipital lobe. For the differences of the two frequency bands, widespread ALFF differences were observed. The ALFF abnormalities in aMPFC/ACC, PCu, right IPL, and some regions of occipital and parietal cortices were greater in the slow-5 band compared to the slow-4 band. Additionally, the THI score of PT patients was positively correlated with changes in slow-5 and slow-4 band in PCu. Pulsatile tinnitus is a disease affecting the neurological activities of multiple brain regions. Slow-5 band is more sensitive in detecting the alternations. Our results also indicated the importance of pathophysiological investigations in patients with pulsatile tinnitus in the future.